CRITERIA FACTOR MODEL OF EFFICIENCY ASSESSMENT OF COMPUTER ORIENTED LEARNING ENVIRONMENT OF AN INSTITUTE OF POSTGRADUATE PEDAGOGICAL EDUCATION - K. Kolos (Kherson State University, 2015)
This article provides rationalization for a comprehensive assessment of computer-oriented learning environment efficiency of an institute of postgraduate pedagogical education and provides definitions of the 'efficiency of computer-oriented learning environment of an institute of postgraduate pedagogical education', and the 'assessment criteria for computer-oriented learning environment efficiency of an institute of postgraduate pedagogical education'. In order to measure the efficiency of computer-oriented learning environment of an institute of postgraduate pedagogical education, a multi-criteria factor evaluation model was created. It includes, in the first place, the factors defining computer-oriented learning environment of an institute of postgraduate pedagogical education. The article provides rationalization for and describes the developed criteria of efficiency assessment in such an environment and divides them into corresponding criterion characteristics as well as establishes the numeric values of coefficients of importance of all characteristics, criteria and efficiency factors of computer-oriented learning environment of an institute of postgraduate pedagogical education.